The Positive Impact of Digitalization On The Indonesia Economy - Gultom, Defitria; Hutabarat, Gabriel Stefanus Pangapul; Dirgantara, Muhamad; Pratama, Rangga; Hidayah, Ayuning (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The development of digitalization has had a positive impact on economic growth in Indonesia, where technology has helped business and trade transactions. This study aims to analyze the positive impact of digitalization on the Indonesian economy. This research uses a qualitative approach in the form of a description of words. The author used desk research. The results show that digitalization has changed many aspects of Indonesian life including the economy. The development of technology and information and communication has played an integral role in improving the country's economic growth. A review of Indonesia's digitalization infrastructure shows that the government is building digital infrastructure to support digital transformation in Indonesia. The result of these developments in the form of technological advances and digitalization has brought about a digital economy characterized by the high development of technology-based businesses and trade transactions. Rp714.4 trillion with 27.6% growth compared to the previous year.